Pengaruh Bermain Playdough Melalui Youtube Terhadap Perkembangan Motorik Halus Di Taman Kanak-Kanak Hang Tuah Padang - Mardiah, Mardiah; Yulsyofriend, Yulsyofriend (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
Fine motor skills are aspects that play an important role in earl@childhood. Good motor/ability@are*drag that use the fingers mini*muscles that*require*eye-hand coordination. The research problem is*that children's*good*motor*ability, especially hand-eye coordination, have not developed optimally when moving their fingers and wrists in Hang Tuah Padang Kindergarten because the training in fine motor skills is still low. The research purpose was to reveal the extent to which the playing playdough through YouTube impact at Hang Tua Padang Kindergarten has on fine motor development. This research uses an approach in quantitative through of quasi-experiments. The research population were all children of Hang Tuah Padang Kindergarten and included a sample of 10 B2 children and 10 B3 children. The technique for data collection uses a test of five-item statement. The techniques for data analysis used the test of normality, homogeneity, and hypothesis by SPSS 25 application with a level in significance of 5% (0.05). The research result shown that playing playdough via YouTube has a more significant effect on the children's good motor ability development. Compared with the control class playing playdough through teacher demonstrations. The research result indicated that the class for experimental had a score in pre-test of 120 and a score in post-test of 176, while the class for control had a score in pre-test of 126 and a score in post-test of 159. With a sig (2-tailed) score of 0.012 <0.05.